The Influence of Product Knowledge, Product Involvement, and Self-Image Congruence on Longchamp Le Pliage Bags Brand Trust (A Study in Surabaya City) - Maladewi, Rara Tatum Sakilla Pasha; Azizah, Nurul (Jurnal Manajemen, 2024)
This research contributes to a deeper understanding of consumer behavior in the luxury goods market, providing valuable insights for businesses aiming to strengthen brand trust and expand their market presence of Longchamp Le Pliage bags in Surabaya City. Employing online questionnaires disseminated among Longchamp Le Pliage bag users in Surabaya, data was meticulously gathered from a sample comprising 144 respondents. Utilizing multiple linear regression analysis, the research unveils that product knowledge emerges as the paramount determinant of brand trust, closely followed by self-image congruence and product involvement. These findings underscore the critical importance of these variables in shaping consumer perceptions of the Longchamp brand.. For enterprises aspiring to fortify consumer trust in their brands, accentuated emphasis on augmenting product knowledge, honing product development strategies, and nurturing self-image congruence emerges as imperative. Furthermore, exploring further factors influencing brand trust is suggested for future research endeavors, aiming to provide a more intricate understanding of consumer behavior within the luxury goods market landscape.